Experimental results of a method of power pulse generation in hammerless hydromechanical drilling system; SGEM. 16th International Multidisciplinary Scientific GeoConference; Bk. 1, vol. 2 - Shadrina A. V. Anastasiya Viktorovna; Saruev A. L. Aleksey Lvovich; Saruev L. A. Lev Alekseevich; Vasenin S. S. Sergey Sergeevich (Exploration and mining, 2016)
Title screen